(untitled) (Research, Society and Development, 2022)
The objective was to investigate the frequency of cardiovascular risk factors (CRF) and cardiovascular complications in hypertensive adults from Maceió-AL, with data from two cross-sectional studies (2007/2009 and 2013/2016). CVRF was analyzed: smoking, physical inactivity, family history, short stature, overweight/obesity (OW/OB), obesity (OB), waist / height ratio (WHR), taper index (TI) and abdominal obesity (AO), and ACV: kidney disease (KD), acute myocardial infarction, coronary disease and stroke. Prevalence ratio was analyzed using Poisson regression, with robust adjustment of variance in crude and multivariate analysis. WHR, AO, TI, OW/OB, physical inactivity and family history had the highest prevalence: 91.59%, 83.17%, 85.85%, 86.33%, 68.44 and 63.64% respectively. Regarding the evolution in the prevalence between the two cuts in the time after adjustment for sex and age, physical inactivity (PR=1,35; CI95%: 1,02-1,77) e OW/OB (PR=1,17; CI95%: 1,04-1,32) showed an increase and WHR (PR=0,87; CI95%: 0,81-0,94) significant reductions. The increase in excess weight and inactivity among hypertensive individuals, even with a reduction in WHR, indicates vulnerability in pressure control in this group at high cardiovascular risk.